2002
DOI: 10.1271/bbb.66.2673
|View full text |Cite
|
Sign up to set email alerts
|

Use of Shark Collagen for Cell Culture and Zymography

Abstract: The uses of shark collagen as a matrix for cell culture and as a substrate for zymography were investigated. Fibroblasts were cultured on a gel matrix of shark type I collagen at 309 C. The collagen gel had contracted by 4 days of incubation. Individualˆbroblasts were visible against the transparent background of the contracted collagen as long, lean star-shaped cells. The matrix metalloproteinases (MMPs) fromˆbroblasts secreted from the medium more easily digested shark gelatin than pig gelatin. MMP-2, -9, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…It has also been reported that shark collagen gel could be used as a cell-culture matrix, but cell culture was conducted at 30°C. The shark collagen gel melted at 37°C although its melting temperature was 39-41°C [15]. Therefore, this is the first report to show successful cell culture at 37°C on fish collagen gel to which no reagents were added to improve the thermal stability.…”
Section: Discussionmentioning
confidence: 88%
“…It has also been reported that shark collagen gel could be used as a cell-culture matrix, but cell culture was conducted at 30°C. The shark collagen gel melted at 37°C although its melting temperature was 39-41°C [15]. Therefore, this is the first report to show successful cell culture at 37°C on fish collagen gel to which no reagents were added to improve the thermal stability.…”
Section: Discussionmentioning
confidence: 88%
“…Shark type I collagen forms fibrils under different conditions compared to bovine and porcine collagen [31]. For example, shark type I collagen gels and membranes have stronger rigidity and higher affinity to water vapour than those of porcine collagen, thus indicating the potential for utilising shark collagen as a new type I collagen material for various uses such as cell culture and medical technology [32].…”
Section: Collagen From Fishmentioning
confidence: 99%
“…To a sample of 3-5 mg of the cross-linked scaffold, 1 ml of 4% (w/v) NaHCO 3 solution (pH 8.5) and 1 ml of freshly prepared 0.5% (w/v) TNBS solution in distilled water was 9 added. After allowing the reaction to take place for 2 h at 40 ℃, 2 ml of 6 N HCl was added, and the temperature was raised to 60 ℃.…”
Section: Determination Of the Degree Of Cross-linkingmentioning
confidence: 99%
“…The structure and physicochemical characteristics of fish collagen have already been investigated (6, 7), but there had been very few studies on the potential for using fish collagen as biomaterials (9). In the present study, we used fish collagen from chum salmon skin, which was discarded as industrial waste, so as to make effective use of natural sources.…”
Section: Introductionmentioning
confidence: 99%